Clarifier with built-in prefilter for water treatment - Govorova Zhanna; Kanivets Uliana; Govorova Anastasia (E3S Web of Conferences, 2023)
Natural water sources in the Northern, Northwestern and other regions of Russia are characterized by increased color, the presence of organic pollutants of natural and anthropogenic origin, as well as often high bacterial contamination. The use in practice of a technological scheme with preliminary chlorination and purification of low-turbid colored waters in clarifiers with suspended sediment and filters during periods of low alkalinity and temperature is not always justified. The consequence is a decrease in the barrier role of structures for organochlorine contamination and residual aluminum. The intensification of the water purification process in clarifiers is achieved by adjusting the reagent treatment mode, artificially increasing the turbidity index of water, the device of flocculation chambers, thin-layer modules or sludge recirculators in the working chamber, as well as the device of a prefilter with floating loading. The description of an experimental stand simulating the operation of an industrial water supply station, parameters and operating modes of a clarifier model with a built-in prefilter is given. The experiments were carried out in different periods of the year on real water with permanganate oxidizability up to 22.3 mg/l, chromaticity – 55-81 degrees, turbidity – 2.8-25.6 FTU, pH from 7.52 to 8.04 and alkalinity 1.5-4.6 mg-eq/L. The results of the study showed that the device of a prefilter with a layer thickness of no more than 0.5 m from polystyrene granules at filtration rates from 1.2 to 1.7 m / h reduces turbidity to 7.9 FTU, chromaticity to 14.5 deg., and permanganate oxidizability by 5.4 mg/l, compared with a single clarifier. At the same time, the load on the second stage structures is reduced and the normative value of residual aluminum in drinking water is ensured.load on the second stage structures is reduced and the normative value of residual aluminum in drinking water is ensured.